An innovative method for manganese (Mn2+) and ammonia nitrogen (NH4+-N) stabilization/solidification in electrolytic manganese residue by basic burning raw material. (August 2020) - Shu, Jiancheng; Li, Bing; Chen, Mengjun; Sun, Danyang; Wei, Liang; Wang, Yao; Wang, Jianyi
Abstract: High concentrations of manganese (Mn 2+ ) and ammonia nitrogen (NH4 + -N) in electrolytic manganese residue (EMR) have seriously hindered the sustainable development of electrolytic manganese industry. In this study, an innovative basic burning raw material (BRM) was used to stabilize/solidify Mn 2+ and NH4 + -N in EMR. The characteristics of EMR and BRM, stabilize mechanism of NH4 + -N and Mn 2+, and leaching test were investigated. The concentrations of NH4 + -N and Mn 2+ were 12.8 mg/L and 0.1 mg/L, respectively, when the solid liquid ratio was 1.5:1, and the mass ratio of EMR and BRM was 100:10, at the temperature of 20 °C reacting for 12 h Mn 2+ was mostly solidified as bustamite ((Mn, Ca)Si2 O6 ), groutite (MnOOH) and ramsdellite (MnO2 ). NH4 + -N was mostly recycled by (NH4 )2 SO4 and (NH4 )3 H(SO4 )2 . Leaching test results indicated that the concentrations of heavy metals were within the permitted level for the integrated wastewater discharge standard (GB8978-1996). Economic evaluation revealed that the cost of EMR treatment was $ 10.15/t by BRM. This study provided a new research idea for EMR harmless disposal. Graphical abstract: Image 1 Highlights: Burning raw material was used to stabilize/solidify Mn 2+ and NH4 + -N in EMR. The concentrations of heavy metals, NH4 + -N meet the discharge standard (GB8978-1996). Mn 2+ was mainly solidified as (Mn, Ca)Si2 O6, MnOOH and MnO2 . NH4 + -N mainly escaped in the form of ammonia. This study provided a new research idea for EMR harmless disposal.